Income Tax Law : as ammended by Law No. 1 of 1958, Law No. 52 of 1958; Law No. 35 of 1959 and Law No. 7 of 1960 - Western Region of Nigeria (Nigeria Western Region Income Tax, 1957)
The Income tax law
No. 16 of 1957
aia 14/03/2019
Loans
Keywords: Income tax; Western Nigeria